Inconsistencies and time delays in site‐specific research approvals hinder collaborative clinical research in Australia. Issue 9 (16th September 2016) - White, V. M.; Bibby, H.; Green, M.; Anazodo, A.; Nicholls, W.; Pinkerton, R.; Phillips, M.; Harrup, R.; Osborn, M.; Orme, L. M.; Conyers, R.; Thompson, K.; et al.
Abstract : Background/Aim: The aim of this study was to describe the time and documentation needed to gain ethics and governance approvals in Australian states with and without a centralised ethical review system. Methods: This is a prospective descriptive study undertaken between February 2012 and March 2015. Paediatric and adult hospitals ( n = 67) in Australian states were approached to allow the review of their medical records. Participants included 15‐ to 24‐year‐olds diagnosed with cancer between 2008 and 2012. The main outcomes measures were time (weeks) to approval for ethics and governance and the number and type of documents submitted. Results: Centralised ethics approval processes were used in five states, with approval taking between 2 and 18 weeks. One state did not use a centralised process, with ethics approval taking a median of 4.5 weeks (range: 0–15) per site. In four states using a centralised ethics process, 33 governance applications were submitted, with 20 requiring a site clinician listed as an investigator. Governance applications required the submission of 11 documents on average, including a Site‐Specific Assessment form. Thirty‐two governance applications required original signatures from a median of 3.5 (range: 1–10) non‐research persons, which took a median of 5 weeks (range: 0–15) to obtain. Governance approval took a median of 6 weeks (range: 1–45). Twelve research study agreements were needed, each taking a median of 7.5 weeks (range: 1–20) to finalise. Conclusion: The benefits of centralised ethics review systems have not been realised due to duplicative, inflexible governance processes. A system that allowed the recognition of prior ethical approval and low‐risk applications was more efficient than a central ethics and site‐specific governance process.